Entre costuras e pedras: feminismo e criação em performance arte - Cairrão, Luana Furtado Ramos (2023)
This master's thesis is anchored in creation in Performance Art, addressing the artist's experience related to her separation from an abusive heteronormative relationship. Thus, the objective of this research was to create a series of performances that weave cross-sectional relationships between art and contexts linked to the author's experiences with feminist studies. The following question was raised: “how to develop a creative process of performances, based on personal memories about separation and abusive relationships, supported by feminist studies?”. Still, there is an important crossing related to the memories of the proponent researcher's great-grandmother, who fought for the right to divorce in the 1940s, a time when it was not yet allowed by Brazilian laws. Her great-grandmother was a renowned seamstress of wedding dresses in 1940. For this reason, the author brings the practice of sewing into her poetics, linked to the stone element as a metaphor for a pain or problem. The incorporation of stones into the poetic referent comes from the experience initially carried out based on a proposal as part of the Laboratory of Performance, Art and Culture (LAPARC) which hosts the research group Performances: art and culture, linked to PPGART-UFSM and CNPQ . The LAPARC collective, in this way, also affects the poetics of the work. Autoethnography was adopted in order to dialogue as the methodological procedure that supports this work. However, strong traces of autobiography also accompany the researcher’s journey. Nine in-person performances were produced that bring the poetics of sewing and stones into their creation and conception processes. In this way, it was possible to transversally involve art, feminist studies, life experiences of the researcher and other women through poetics in performance.